Expression and subcellular localization of a novel gene Bm-X of the silkworm, Bombyx mori - Lv, Zhengbing; Liu, Yunlong; Chen, Ying; Li, Bo; Liu, Lili; Chen, Jian; Nie, Zuoming; Sheng, Qing; Yu, Wei; Zhang, Yaozhou (Scientific Research Publishing, 2012)
According to the large-scale sequencing of cDNA library from silkworm pupae, the cDNA of a novel gene with blank research background was identified and temporarily named Bm-X. The length of this cDNA is 778 bp. We obtained its ORF for further study by bioinformatics analysis. It is 444 bp and encodes 147 amino acid residues, with a predicted molecular weight (MW) of 16.4 kD and an isoelectric point (pI) of 3.69. In this study, we successfully constructed a recombinant plasmid pET-28a(+)-Bm-X and expressed it in Escherichia coli. We used the fusion protein rBm-X which purified by Niaffinity chromatography to produce polyclonal antibodies against Bm-X for Western blot analysis. The analysis revealed that Bm-X was expressed in the larval midgut, the epidermis and the silk gland. In addition, the subcellular localization analysis of silkworm ovary epithelial cells (BmN cells) showed that Bm-X protein was located both in cytoplasm and nucleus, and the signal was stronger in cytoplasm than in nucleus. Our findings indicate that Bm-X gene is a novel species-specificity gene and its expression product can be detected in tissues of the fifth silkworm instar larvae and BmN cells.
Keywords: Bombyx Mori; Novel Gene; Expression; Subcellular Localization; Bm-X